PELATIHAN TATA KELOLA PEMERINTAHAN DESA BENTEK UNTUK PERANGKAT DESA BENTEK OLEH PROGRAM STUDI ILMU PEMERINTAHAN UNIVERSITAS 45 MATARAM: Village Governance Training for Village Officials in Bentek Village by the Government Science Study Program at 45 Mataram University - Putra, Sandi Justitia; Zulhadi, Zulhadi; Mandini, Denda Devi Sarah; Rahmandari, Ismi Arifiana; Sujudi, Anis; Arisandy, Rita; Kahfi, Rido Ashabul; Sumajayadi, Sumajayadi; Umar, Mubarak; Bukhari, Ahmad Saifuddin (Yayasan Al-Amin Qalbu, 2024)
Community service activities in the form of village governance training organized by the Mataram 45 University Government Science Study Program for village officials in Bentek Village aim to increase the capacity and understanding of village officials in managing village government effectively and transparently. Training methods include theoretical presentations, case studies, as well as discussion sessions and direct practice to apply Good Governance concepts. Evaluations are carried out to measure the increase in knowledge and skills obtained by participants, as well as their impact on the efficiency and accountability of village government. The results show a significant increase in the understanding and practice of village governance in Bentek Village, illustrating the commitment of the Mataram University 45 Government Science Study Program in supporting village government capacity building in Indonesia